Diagnosis-Related Group Weight and Derived Case Mix Index to Assess the Complexity among Twins - Joya, Rikizam M.; Cottrell, Lesley; Kiefer, Autumn; Polak, Mark J. (American Journal of Perinatology, 2020)
Objective Diagnosis-related groups (DRGs) are used to summarize hospital morbidity and mortality. Each DRG has a weight which is important in calculating the case mix index (CMI), a numeric summary of disease complexity in a population of patients. We utilized DRG weight and resultant CMI to compare postnatal outcomes among singletons versus monochorionic and monoamniotic, monochorionic diamniotic, and dichorionic diamniotic twins.Study Design This single-center and retrospective cohort study evaluated DRGs assigned by the investigators, birth weight, gestational age, length of stay (LOS), NICU admission rate, and mortality in twin births between 2014 and 2016. Twins were analyzed depending on chorionicity and amnionicity. Overall, 3 months of singleton births served as the control. The CMI derived from DRG weights were compared across groups.Results Twins (n = 288) had lower gestational ages and birth weights and higher mortality, LOS, NICU admission rates and DRG weights/CMI compared with singletons (n = 327; p < 0.001 for each). The LOS was no different between twin subtypes; monochorionic monoamniotic twins had the highest mortality and DRG weight (p < 0.001).Conclusion DRG weight and CMI values summarize in-hospital complexity and can be a useful tool to evaluate differences in care complexity among groups of patients.Key Points
Keywords: diagnosis-related group; case mix index; twins; neonatology